2019
DOI: 10.3390/ijerph16061015
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Power Type, Work Engagement, and Organizational Citizenship Behaviors

Abstract: The focus of this study is to investigate if power type improves organizational citizenship behavior (OCB) through work engagement. Based on existing research, power can be classified into two main types: coercive and non-coercive power. Coercive power is divided into the categories of coercion, reward, and legitimate power, and non-coercive power can be divided into information, expert, and reference power. Therefore, this study examines what kind of relationship is formed in the work engagement of organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(21 reference statements)
0
13
1
1
Order By: Relevance
“…Second, members must be trusted to play their assigned roles. Third, members must engage in creative and voluntary activities that go beyond their set roles [24].…”
Section: Ocbmentioning
confidence: 99%
“…Second, members must be trusted to play their assigned roles. Third, members must engage in creative and voluntary activities that go beyond their set roles [24].…”
Section: Ocbmentioning
confidence: 99%
“…29 Another study of 184 employees reported that organizational citizenship behavior is positively related to team-member exchange and to servant leadership. 30 Likewise, reports have found a positive relationship between organizational citizenship tasks and work engagement, 5,6 which leads to organization effectiveness. 5 However, other reports suggest engaging in citizenship tasks does not outweigh the negative consequences for career advancement due to the time spent on such tasks.…”
Section: Discussionmentioning
confidence: 98%
“…30 Likewise, reports have found a positive relationship between organizational citizenship tasks and work engagement, 5,6 which leads to organization effectiveness. 5 However, other reports suggest engaging in citizenship tasks does not outweigh the negative consequences for career advancement due to the time spent on such tasks. 6,29 For example, physicians in academic medicine who serve on multiple committees may not be as productive in publishing research and thus may not meet traditional criteria used for promotion, such as number of publications, citations, and Hirsch-index.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations